Language as pride, love, and hate: Archiving emotions through multilingual Instagram hashtags. (April 2018) - Lee, Carmen; Chau, Dennis
Abstract: This paper examines multilingual hashtags as discourse of emotions about social movements, with a focus on the 2014 Umbrella Movement in Hong Kong. With the Chinese search word #雨傘運動 ("Umbrella Movement"), over 9000 hashtags were collected from 700 posts on Instagram. These hashtags were coded by language choice and their broad discourse functions of fact, opinion, and emotion. Our analysis suggests that while stating facts and expressing opinions, a significant proportion of Instagram hashtags about the Umbrella Movement are also affective in function (e.g. #ilovehongkong, #hate). These hashtags convey emotions associated mainly with political demands, solidarity, unity, hatred, frustration, and dissatisfaction. We also conducted online interviews with selected Instagram users to understand better their multilingual hashtagging practices and language attitudes. Overall, the present study suggests that affect was expressed and experienced through a common set of linguistic resources - Cantonese, mixed code, and traditional Chinese characters - which then became codes of unity and solidarity in difficult times. Interviewees also produced discourses of pride in Cantonese which further suggest the use of Cantonese in asserting their unique Hongkonger identities. Drawing on Ahmed's (2004) notion of 'affective economies', this article concludes by unravelling the relationship between language, emotion, digital technologies, and politics.